Patient Satisfaction with Hospital Health Care Services: Outpatient Settings of Combined Military Hospital Bogra - Munir, AKM Mashiul; Halim, AKM Yunus (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: In many developing countries, accreditation programs, which have been implemented as a regulatory tool to ensure quality of service and efficient use of resources. To improve the quality of services, health organizations use patient satisfaction survey to evaluate their processes delivered. The care in the Out Patient Department (OPD) indicates the quality of services of any hospital. Combined Military Hospital (CMH) Bogra, is the largest tertiary level military hospital in North Bengal. Objective: To assess the satisfaction levels of patients‘ in CMH Bogra related to health care services. Materials and Methods: A cross sectional study was carried out among 367 patients attending outpatient department of CMH Bogra. The patients were selected randomly from out patient department. The study was conducted from 01 May 2015 to 31 October 2015. All patients were interviewed using pre-structured questionnaire, which included various variables related to patient satisfaction. Results: A total number of 367 respondents were interviewed. Majority (48.2%) of the respondents were from the age category of 26-35 years. Maximum attending population consisted of Army personnel. Overall satisfaction level of patients on hospital services was good. Requirement of separate waiting room for the JCO’s and training of the hospital staffs on behaviour with the patients were found important. Conclusion: Patient satisfaction surveys have evolved as a powerful management and marketing tool. It is being widely used by various hospitals to capture the “Voice of the Consumer”. Among the respondents, 95% of expressed overall satisfaction. This bears a testimony to the efforts of the hospital management towards improvement of services. Journal of Armed Forces Medical College Bangladesh Vol.11(2) 2015: 61-68